Odontogenic infections: Microbiology and management - Rashi Bahl; Sumeet Sandhu; Kanwardeep Singh; Nilanchal Sahai; Mohita Gupta (Wolters Kluwer Medknow Publications, 2014)
Objective: The aim of this retrospective study was to evaluate the involvement of fascial spaces, their bacteriology, sensitivity to antibiotics and management of odontogenic infection in 100 patients of age less than 60 years. Results: The mandibular 3 rd molar was found to be the most commonly offending tooth, followed by the mandibular 2 nd molar. The submandibular space was the most frequently involved fascial space both in single fascial space infections and multiple fascial space infections. Mixed growth (aerobic and anaerobic) was seen in culture smears of 60 patients, only aerobic bacterial growth was seen in 25 patients and anaerobic bacterial growth was seen in culture smears of 15 patients. Streptococcus viridans was the most frequently isolated bacteria among the aerobes, whereas Bacteroides and Prevotella were the most common bacterial species among anaerobes. Empirical antibiotic therapy in the form of Co amoxiclav and Metronidazole was given. Incision and drainage followed by extraction of the offending tooth/teeth was carried out. Conclusion: It was concluded that odontogenic infections were mixed aerobic-anaerobic infections. Anaerobic as well as aerobic cultures were necessary to isolate all pathogens. Successful management of these infections depends on changing the environment through decompression, removal of the etiologic factor and by choosing the proper antibiotic.